The Role of Media Literacy in Countering Misinformation - Hamzeh, Dana (2023)
The COVID-19 pandemic revealed a major online misinformation problem and a discourse on conspiracy theories that have influenced youths’ attitudes towards vaccination. This thesis aims to examine the role of media literacy in combating misinformation and conspiracy theories related to COVID-19 vaccination. Equipping the youth with media literacy skills helps them read critically, assess media texts, verify the accuracy of information from different sources, and deepen their knowledge about the construction of these media texts. In addition, media literate youth can critically reflect on the truthfulness and intentions behind media content and identify pervasive conspiracy theories. The method used in this study is a cross sectional, self-administrated, face-to-face survey completed by 819 students in five universities across Lebanon. The study assesses the relationship between media literacy, beliefs in conspiracy theories surrounding COVID-19, and vaccine hesitancy. It highlights the importance of implementing digital media literacy within the educational system to enable the young generation to fight the negative consequences of social media. Results indicate a significant positive association between youth media exposure and them believing in COVID-19 conspiracy theories. They also reveal a significant positive association between media illiteracy and the youth's tendency to believe in COVD-19 conspiracy theories. Unexpectedly, the results also show that a portion of the participants still engage in information verification despite trusting media.